Supply-side sustainability - Allen, T. F. H. (Columbia University Press, 2003)
While environmentalists insist that lower rates of consumption of natural resources are essential for a sustainable future, many economists dismiss the notion that resource limits act to constrain modern, creative societies. The conflict between these views tinges political debate at all levels and hinders our ability to plan for the future. Supply-Side Sustainability offers a fresh approach to this dilemma by integrating ecological and social science approaches in an interdisciplinary treatment of sustainability. Written by two ecologists and an anthropologist, this book disc.
Keywords: Ecology.; Sustainable development.; Développement durable.; sustainable development.; SCIENCE -- Environmental Science (see also Chemistry -- Environmental); NATURE -- Ecosystems & Habitats -- Wilderness.; NATURE -- Ecology.; SCIENCE -- Life Sciences -- Ecology.; SCIENCE -- Environmental Science.; Ecology; Sustainable development